Sol gel synthesis and photoluminescence study of Eu3+ doped SnO2 - Bajpai, Namrata; Khan, S A; Kher, R S; Brahme, Namita; Dhoble, S J (Recent Research in Science and Technology, 2012)
Tin oxide(IV) nanophosphor doped with europium had been prepared by sol-gel technique using SnCl4 as precurser. XRD, IR, SEMand TEM analyses were used for characterization of SnO2:Eu3+. The XRD analysis shows that well crystallized tetragonal rutile SnO2:Eu3+ can be obtained by this method and the crystal size was about 15-20nm as an average for the sample calcined at 400ºC for 2h. The evolution of the most important functional groups during the steps involved in this synthesis route is explained in view of the results obtained with FTIR and XRD. A spherical like morphology of the prepared SnO2 nanoparticles was observed in the SEM and TEM studies. The SnO2 nanoparticles show stable photoluminescence emission intensity at 612 nm (5D0/7F2) of the Eu3+ ions activated SnO2 nanocrystals This paper discuss the mechanistic approach of origin of luminescence in SnO2.